Human Leukocyte Antigen Genetic Variations in Obstructive Sleep Apnea Patients that were positive for HLA-DQB1*0602. - Qatarneh, ThamerA Fattah Al; Mohammad Momany, Suleiman; Mohammad Abuharfil, Nizar; Mahasneh, Amjad Abduallah; Khader, Yousef Saleh; Daoud, Ammar Khaled (Bangladesh Journal of Medical Science, 2019)
Background: Genetic variations in the HLA system may cause susceptibility to a large number of autoimmune and infectious diseases, and the complexity of HLA makes it hard to investigate HLA types associated with diseases. The association between HLA and Obstructive Sleep Apnea (OSA) is not well investigated due to the complexity of OSA pathogenesis; including genetic and non-genetic in different populations. Our previous study using PCR-SSPs technique showed that HLA-DQB1*0602 allele is associated with almost 6 times increase in risk in North Jordan OSA patients. Aim: The aim of this study was to see if there are any HLA genetic variations using DNA sequencing technique in the region in which HLA-DQB1*0602 is located that might interact with HLA-DQB1*0602 and affect OSA development in OSA patients who were positive for HLA-DQB1*0602 allele. Result: The DNA sequencing results showed 8 nucleotide substitution variations, which are p.G77E (c.230G>A), p.R80R (c.240C>G), p.Q85L (c.254A>T), p.R87P (c.260G>C), p.Y69D (c.205T>G), p.A70V (c.209C>T), p.A70A (c.210G>A), p.Y79Y (c.237C>T). Although only 5 variants resulted in amino acid change, all 8 variants were included in the statistical analysis, and none of these genetic variants was significant (p-value> 0.05). Additionally, eight haplotypes were detected. Some of these haplotypes might have a role in disease development through the interaction with HLA-DQB1*0602 and other genetic variants or could be as markers for OSA by the mechanism of linkage disequilibrium. Conclusion: Further studies are needed to explain the pathogenesis of OSA in terms of possible self or non-self-antigens involved. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.473-478